1983
DOI: 10.1557/proc-27-413
|View full text |Cite
|
Sign up to set email alerts
|

Ion Implantation of Polymers

Abstract: Ion implantation provides a mechanism for radically modifying the electronic and transport properties of a variety of polymers that are normally insulating.By using masks and tailoring the implanted species and ion energies, conducting paths in an insulating medium can be fabricated between specific reference points, an application of obvious relevance to the microelectronics industry.Specific results are reported for modification of the structure, electrical conductivity, thermoelectric-power, optical transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Many insulating polymers were observed that a chemical modification seems more important in the fluence range between 10 12 cm À2 and 10 14 cm À2 and depends on the ion species implanted, while a fluence above 10 15 cm À2 generates structural defects and leads to the formation of carbonaceous materials. 2,3,7 Furthermore, implantation of ion metals in insulating polymers is an effective method to produce metallic or metal-oxide nanoparticles in polymers and to modify the polymer structure giving rise to the formation of novel polymer nanocomposites. At high fluences, the nucleation of nanoparticles may occur due to the high metal cohesive energy and the low metal-polymer interaction energy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many insulating polymers were observed that a chemical modification seems more important in the fluence range between 10 12 cm À2 and 10 14 cm À2 and depends on the ion species implanted, while a fluence above 10 15 cm À2 generates structural defects and leads to the formation of carbonaceous materials. 2,3,7 Furthermore, implantation of ion metals in insulating polymers is an effective method to produce metallic or metal-oxide nanoparticles in polymers and to modify the polymer structure giving rise to the formation of novel polymer nanocomposites. At high fluences, the nucleation of nanoparticles may occur due to the high metal cohesive energy and the low metal-polymer interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…Both the formation of amorphous carbon and carbonaceous materials and the metal nanoparticle formation modify the electronic transport properties significantly, and an increase of the conductivity can be observed. 3,4,7,[9][10][11][12] The realization of metalcarbon-polymer nanocomposite structures by metal-ion irradiation opens the door for potential applications in various technological fields such as electronics, magnetics, optoelectronics, optics, and mechanics but also applications in biological and medical fields may become feasible. 1,[7][8][9][13][14][15][16][17] In addition, it should be noted that metalcarbon-polymer nanocomposite films may exhibit interesting pressure-sensitive, catalytic, and gas sensing properties and are promising candidates for the realization of efficient flex, catalytic, and gas sensor devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ion bombardment and implantation have been widely used to alter the electrical properties of polymers and the results have been reviewed elsewhere [1][2][3]. Ion implantation produces accurate location of dopant depth and doping with ions that cannot be achieved chemically.…”
Section: Introductionmentioning
confidence: 99%